Indian women journalists' responses to sexism and sexual harassment - Chadha, Kalyani; Steiner, Linda; Guha, Pallavi (International Communication Research Journal, 2017)
Gale Academic OneFile includes Indian women journalists' responses to sexism and by Kalyani Chadha, Linda Steiner, and Pall. Click to explore.
Publisher: International Communication Division (ICD), of AEJMC
Keywords: Myriam; journalism

Damaging and daunting: female journalists’ experiences of sexual harassment in the newsroom - North, Louise (Feminist Media Studies, 2016)
Female journalists’ experiences of sexual harassment are barely documented in the literature about Australian news journalism despite evidence of its ongoing prevalence. There have been some stories of harassment detailed in autobiographies by female journalists and the occasional article in the mainstream media about individual incidents, but it wasn’t until 1996 that a union survey provided statistical evidence of an industry-wide problem. That Media, Entertainment and Arts Alliance survey found that more than half of the 368 female participants had experienced sexual harassment at work. In 2012, I conducted the largest survey of female journalists in Australia finding that there was an increased number of respondents who had experienced sexual harassment in their workplaces. In a bid to better understand female journalists’ experiences of sexual harassment, this paper analyses written comments made by survey participants in relation to key questions about harassment. It finds that most downplay its seriousness and do not make formal reports because they fear victimisation or retaliation. As a consequence, a culture of secrecy hides a major industry problem where many women believe they should work it out themselves and that harassment is the price they have to pay for working in a male-dominated industry.
Publisher: Routledge _eprint: https://doi.org/10.1080/14680777.2015.1105275
Keywords: Myriam; Sexual harassment; female journalists; gender and work; gendered newsrooms; survey of Australian female journalists